2013
DOI: 10.1002/qua.24415
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of nonsteroidal antiinflammatory drugs, naproxen and relafen, in a lipid bilayer membrane

Abstract: Naproxen and relafen, as nonsteroidal antiinflammatory drugs, were simulated in neutral and charged forms and their effects on a lipid bilayer membrane were investigated by molecular dynamics simulation using Groningen machine for chemical simulations software (GROMACS). Simulation of 10 systems was performed, which included different dosages of the drug molecules, naproxen and Relafen, in charged and neutral forms, and a mixture of naproxen and Relafen in neutral forms. The effects of the mixture and the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…One strategy is to use different concentrations of the drug or to even study the simultaneous effect of different drugs, as performed by [270]. They showed a dosage-dependent effect, and they concluded that drug mixtures have a larger effect even at a lower dosage compared to the dosage needed for a single drug [270].…”
Section: Toxic Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…One strategy is to use different concentrations of the drug or to even study the simultaneous effect of different drugs, as performed by [270]. They showed a dosage-dependent effect, and they concluded that drug mixtures have a larger effect even at a lower dosage compared to the dosage needed for a single drug [270].…”
Section: Toxic Effectsmentioning
confidence: 98%
“…Importantly, it should be noted that for some studies, a single drug molecule is used; hence, it is unlikely that meaningful perturbations in the membrane can be observed [304]. One strategy is to use different concentrations of the drug or to even study the simultaneous effect of different drugs, as performed by [270]. They showed a dosage-dependent effect, and they concluded that drug mixtures have a larger effect even at a lower dosage compared to the dosage needed for a single drug [270].…”
Section: Toxic Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Molecular dynamics simulations may provide valuable complementary to experiments information about details of interactions between the molecules. 3 ,14 However, despite enormous growth of the number of studies on computer simulations of lipid bilayers and utilizing GROMACS package for MD simulations (for example, see recent reviews, [15][16][17][18] ) there are no investigations on computer modelling of analgesics in lipid bilayers. Also the interaction between Paracetamol (acetaminophen) and two model membranes made of DPPC and dimyristoylphosphatidylcholine (DMPC) molecules in their liquid crystalline states has been probed.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic potential (EP) across the membrane is one of the most important properties of lipid bilayers that can affect the mechanism of a voltage-gated ion channel. One reason for the appearance of this potential is the orientation of water dipoles and lipid headgroup dipoles at the water-membrane interface (Mojumdar & Lyubartsev, 2010;Yousefpour et al, 2013). The EP can be influenced by the presence of ions and other charged components (H€ ogberg & Lyubartsev, 2008).…”
Section: Electrostatic Potentialmentioning
confidence: 99%